Protura from Yintiaoling National Nature Reserve, Southwest China (Arthropoda, Hexapoda) - Bu, Yun; Gao, Yan; Su, Ya; Jin, Ya-Li (Zootaxa, 2025)
The Protura from Yintiaoling National Nature Reserve, Southwest China, were investigated for the first time. In total, 19 species from four families were discovered. Two species are new to science: Kenyentulus yintiaolingensis sp. nov. and Eosentomon wuxiense sp. nov. Berberentulidae and Eosentomidae are dominant groups, with 15 species. The new species are described and illustrated, and the checklist of 19 species of Protura found in the reserve is also provided.